Artificial Cavities in the Northern Campania Plain: Architectural Variability and Cataloging Challenge - Marco Vigliotti; Maria Assunta Fabozzi; Carla Buffardi; Daniela Ruberti (Heritage, 2023)
In Campania (southern Italy), the widespread presence of anthropogenic cavities in the subsoil of the Neapolitan and Caserta provinces is well known. In these towns, the underground quarrying activities were performed for centuries to extract volcanic tuffs for buildings. The urban developments have sealed many signals of the presence of cavities and their real extent is almost unknown, thus representing a geological hazard and contributing to the subsoil instability of many places. This contribution will show the main cavity typologies recognized across an area north of Naples according to the geological characteristics of the subsoil. The main aim of the study is the cataloging of the cavities and the analysis of the city subsoil as their presence may easily trigger the collapse of the shallow or deeper soils. Moreover, the recognition and sustainable reuse of cavities contributes to enhancing the cultural and touristic promotion of a territory. In this study, a database framework was elaborated that includes all the possible architectural, geological and geotechnical elements of the cavities. Data were managed in a GIS environment in order to provide a useful tool for monitoring and managing the cavities for risk mitigation and tourism enhancement.